2021
DOI: 10.1007/s00423-021-02182-0
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal blood flow in the remaining rectal stump is more affected by total than partial mesorectal excision in patients undergoing anterior resection: a key to understanding differing rates of anastomotic leakage?

Abstract: Purpose Anterior resection is the procedure of choice for tumours in the mid and upper rectum. Depending on tumour height, a total mesorectal excision (TME) or partial mesorectal excision (PME) can be performed. Low anastomoses in particular have a high risk of developing anastomotic leakage, which might be explained by blood perfusion compromise. A pilot study indicated a worse blood flow in TME patients in an open setting. The aim of this study was to further evaluate perianastomotic blood perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In another study, the blood flow measurements with laser Doppler flowmetry were made preoperatively and postoperatively, aiming to compare blood flow changes around the anastomosis in relation to total mesorectal excision (TME) and partial mesorectal excision (PME). 67 The results showed that TME group had a decreased blood flow of the rectum postoperatively than PME group, which may indicate the different AL rates in TME and PME.…”
Section: Surgery-related Factorsmentioning
confidence: 84%
“…In another study, the blood flow measurements with laser Doppler flowmetry were made preoperatively and postoperatively, aiming to compare blood flow changes around the anastomosis in relation to total mesorectal excision (TME) and partial mesorectal excision (PME). 67 The results showed that TME group had a decreased blood flow of the rectum postoperatively than PME group, which may indicate the different AL rates in TME and PME.…”
Section: Surgery-related Factorsmentioning
confidence: 84%
“…Adequate perfusion is essential for a successful colorectal anastomosis, where excessive tension would decrease blood flow and subsequently risk ischemia. Numerous endeavors have strived to show how marginal artery bleeding, 20 colonic perfusion by fluorescence angiography, 21 and rectal laser Doppler flowmetry 22,23 can be utilized to detect insufficient blood flow. While some of these methods are promising, sufficient data do not exist to prove any clinical benefit of their use.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the lower anastomosis means higher risk of anastomotic dehiscence; secondly, the wider gap and fewer tissues surrounding the supra‐levator ani space can contribute to making AL difficult to localize and be wrapped. Additionally, for ISR, there are few arterial branches in the distal rectum, 31 and surgical procedures will inevitably damage the blood supply of the distal rectum, 32 resulting in chronic ischemia of the distal rectum that can be strikingly unfavorable for anastomosis healing. Therefore, AL after ISR will be more critical and less likely to heal spontaneously, and persistent infection will lead to chronic presacral sinus formation or perforation of adjacent tissues forming rectoperineal fistula, rectovesical fistula, and even rectourethral fistula.…”
Section: Discussionmentioning
confidence: 99%